Unrecorded Tundra Fires of the Arctic Slope, Alaska USA - Miller, Eric A.; Jones, Benjamin M.; Baughman, Carson A.; Jandt, Randi R.; Jenkins, Jennifer L.; Yokel, David A. (Fire (Basel, Switzerland), 2023)
Few fires are known to have burned the tundra of the Arctic Slope north of the Brooks Range in Alaska, USA. A total of 90 fires between 1969 and 2022 are known. Because fire has been rare, old burns can be detected by the traces of thermokarst and distinct vegetation they leave in otherwise uniform tundra, which are visible in aerial photograph archives. Several prehistoric tundra burns have been found in this way. Detection of tundra fires in this sparsely populated and remote area has been historically inconsistent and opportunistic, relying on reports by aircraft pilots. Fire reports have been logged into an administrative database which, out of necessity, has been used to scientifically evaluate changes in the fire regime. To improve the consistency of the record, we completed a systematic search of Landsat Collection 2 for the Brooks Range Foothills ecoregion over the period 1972–2022. We found 57 unrecorded tundra burns, about 41% of the total, which now numbers 138. Only 15% and 33% of all fires appear in MODIS and VIIRS satellite-borne thermal anomaly products, respectively. The fire frequency in the first 37 years of the record is 0.89 y−1 for natural ignitions that spread ≥10 ha. Frequency in the last 13 years is 2.5 y−1, indicating a nearly three-fold increase in fire frequency.